2014
DOI: 10.1097/shk.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Is Not a Plasma Ultrafiltrate

Abstract: Studies on animal models have documented a role for the water soluble protein fraction of mesenteric lymph as a conduit from hemorrhagic shock to acute lung injury and post-injury multiple organ failure. We hypothesize that mesenteric lymph is not an ultrafiltrate of plasma and contains specific protein mediators that may predispose patients to ALI/MOF. Mesenteric lymph and plasma were collected from critically ill or injured patients and from nine patients with lymphatic injuries, during semi-elective spine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Proteomic analysis of plasma from patients who have suffered blunt trauma and subsequently developed ALI/MOF, has identified a number potential pro-inflammatory mediators responsible for lung injury, specifically α-enolase and thrombin as well as concomitant decreases in anti-proteases (31;32). Recently, identical proteomic analyses of the plasma from rats that underwent hemorrhagic shock demonstrated that α-enolase significantly increased; moreover, these identical proteins are also found in stored, but not fresh, PRBCs, which may be used to resuscitate these injured patients (7;31).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of plasma from patients who have suffered blunt trauma and subsequently developed ALI/MOF, has identified a number potential pro-inflammatory mediators responsible for lung injury, specifically α-enolase and thrombin as well as concomitant decreases in anti-proteases (31;32). Recently, identical proteomic analyses of the plasma from rats that underwent hemorrhagic shock demonstrated that α-enolase significantly increased; moreover, these identical proteins are also found in stored, but not fresh, PRBCs, which may be used to resuscitate these injured patients (7;31).…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics analysis of lymph has revealed that the composition of proteins in lymph, while having some overlap with plasma, is significantly diverse in protein composition. Quantitatively, there are proteins and peptides that have significantly different concentrations from those in plasma, or even have never before found in plasma (296, 463, 588, 616, 705, 855, 1185). Protease inhibitors, γ-fibrinogen, proteins related to lipid transport and metabolism, and proteins related to innate immunity were found to be more abundant in rat mesenteric lymph than in plasma (705, 1185).…”
Section: Interstitial Flow and Lymph Formationmentioning
confidence: 99%
“…Time dependent events in hemorrhagic shock models in rats are also evidence, such as an early decrease in Ser protease activity, a gradual increase in serpins, and progressive increase in activity of MMPs and ECM proteins, producing an overall protease/antiproteases impaired homeostasis (225). Assessment of human mesenteric lymph obtained after traumatic injury and shock has revealed a variety of proteins suggesting coagulopathy, lysis of cells including erythrocytes, inflammation, extracellular matrix remodeling, immunomodulation, and changes in energy and redox metabolism (296, 297). In a rat model of sepsis (cecal ligation and puncture), proteomic analysis of mesenteric lymph revealed 158 proteins significantly changed, including elevations in ApoE, annexin-1, S100A8/9, and the lipocalin NGAL (1208).…”
Section: Interstitial Flow and Lymph Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analyses of the lymph reveal that the lymph is not merely a plasma ultrafiltrate (Leak et al, 2004; Dzieciatkowska et al, 2014) and that in physiological conditions, the lymph proteome reflects the tissue it originates from and carries a pool of tissue-derived self-antigens important for immunological tolerance (Clement and Santambrogio, 2013; Clement et al, 2016). Similarly, during inflammatory conditions, the lymph mirrors the tissue inflammatory signature.…”
Section: Introductionmentioning
confidence: 99%